The assessment of the utility and impact of sexual assault evidence collection kits (SAECKS) as DNA evidence in suspected cases of rape - Cupido, Danielle (Division of Forensic Medicine and Toxicology, 2015)
The results from this study show the value of good basic medical practices in documentation of injuries, rather than more costly DNA evidence, in assisting courts in rape cases. However, the researchers do argue that in South Africa, as a middle-income country with a high percentage of non-intimate partner rapes, there would be an advantage in improving the system to collect and analyse DNA evidence rather than abandoning it completely. These results taken together suggest that DNA evidence can assist in signifying that sexual act has transpired however it is more likely that convictions will occur if evidence of physical injury is available, as DNA evidence cannot reveal if consent was obtained or not. As stated above South Africa has one of the highest rates of rape worldwide.